THE LOSS OF THE MOTHERLY ROLE IN JAMES’ LIFE: A PSYCHOANALYSIS STUDY ON CHARLES FORSMAN’S THE END OF THE F***ING WORLD - Febriastuti, Farrah (Acitya Wisesa: Journal of Multidisciplinary Research, 2023)
There are several things that might become the aftermath of someone’s trauma. It might influence someone’s capability to form any social interaction with other people or even how someone feel about themselves. To cope with their own trauma, one usually does something unconsciously to make them feel better, as a normal effort that might be carried out by someone to protect their selves from being hurt. This is qualitative research where the data are taken from a graphic novel entitled The End of the F***ing World by Charles Forsman. Sigmund Freud’s psychoanalysis will be used as the grand theory to analyse the character’s core issue, especially for the part of psychosexual development and defense mechanism. This research aims to discuss about James, the main character in The End of the F***ing World, who is struggling with his surroundings as the effects of his childhood trauma. This research reveals that James’ core issue is Oedipus complex and unstable sense of self, which is strongly associated with his trauma of witnessing his mother’s suicide. The loss of his mother has also affected James’ personality as well that he got stuck in his phallic stage and became mother-fixated. Since James did not successfully resolve his phallic stage, his tripartite model becomes imbalance. When the id in himself started to become too demanding, James let out his defense mechanism, which are displacement and repression.